NIR–IFU observations of the merger remnant NGC 34. Issue Volume 15:Issue S359(2020) (March 2019) - Motter, Juliana C.; Riffel, Rogério; Ricci, Tiago V.; Dametto, Natacha Z.; Dahmer-Hahn, Luis G.; Diniz, Marlon R.; Riffel, Rogemar A.; Pastoriza, Miriani G.; Rodríguez-Ardila, Alberto; Storchi-Bergmann, Thaísa; Ruschel-Dutra, Daniel
Abstract: Understanding the interplay between the phenomena of active galactic nuclei (AGN) and starbursts remains an open issue in studies of galaxy evolution. The galaxy NGC 34 is the remnant of the merger of two former gas-rich disc galaxies and it also hosts a strong nuclear starburst. In this work, we map the ionized and molecular gas present in the nuclear regions of the galaxy NGC 34 using adaptive optics (AO) assisted near infrared (NIR) integral field unity (IFU) observations. Our main goals are to better constrain the energy source of this object and to use NGC 34 as a laboratory to probe the AGN-starburst connection in the context of galaxy evolution and AGN feeding and feedback processes.